OPTIMIZATION OF BURGLARY INVESTIGATIONS THROUGH THE ROLE OF IDENTIFICATION DEPARTMENT OF CRIME INVESTIGATION UNIT OF THE PATI POLICE DISTRICT FOR INCREASING CRIME CLEARANCE IN REALIZING PRESISI LAW ENFORCEMENT - Bhaskara Nasution (Advances in Police Science Research Journal, 2022)
ABSTRACT OPTIMIZATION OF BURGLARY INVESTIGATIONS THROUGH THE ROLE OF IDENTIFICATION DEPARTMENT OF CRIME INVESTIGATION UNIT OF THE PATI POLICE DISTRICT FOR INCREASING CRIME CLEARANCE IN REALIZING PRESISI LAW ENFORCEMENT Bhaskara A.A.Nasution, No Ak .18.157,baskara.nasution@gmail.com Behind the high number of burglary cases but low crime clearance. Crime Investigation Unit of Pati Police District is required to improve the performance of PRESISI law enforcement following the mandate of Police Chief General Listyo Sigit Prabowo, M.Si. In the implementation of the burglary investigation. There is an element in the function of the crime investigation unit that is missing. This element is the function of police identification. This function was carried out by the identification department of the crime investigation unit Pati Police as the first investigator who should carry out the crime scene. But in fact, the identification department of crime investigation of the Pati Police district does not have an active role in the burglary investigation. The results of the study conducted by the authors show that the settlement of burglary criminal acts through the role of Uridentification is still relatively lacking because the identification department in Pati police district usually only helps to handle murder cases or helps with the task of registering fingerprints so for SKCK manufacturing services. This is due to the lack of competent members, systems, and methods that are not implemented properly, and the lack of cooperation carried out. For this reason, optimizing the role of the Identification department in conducting burglary criminal investigations needs to be carried out by improving competent human resources, revamping systems and methods of carrying out tasks, and building cooperation to help improve crime clearance to realize PRESISI law enforcement in the Pati area.